Synthesis, characterization and gene expression of novel bis-Schiff base compounds and study their anti-bacterial activity using different genes - Mohammed Adnan Abid; Mustafa A-Jabbar Al-Jumaili; Ali Adnan Abed (Results in Chemistry)
New Schiff compounds based on benzidine (Seven compounds, A–G, 80–90 %) are prepared from the condensation of seven aromatic aldehydes. These agents were characterized by 13C, 1H NMR, HRMS, FTIR, and M.P. The potency of these compounds was examined against Escherichia coli (E. coli). Compounds A–G show the optimal results by the bacterial growth inhibition, where MIC values were 8, 32, 16, 128, 2, 8 and 8 μg/mL respectively. The gene expression using qRT-PCR has been determined. The two genes of E. coli (oxyR1 and perR) expressed downregulated when treated with all compounds, specifically A and E. These genes are control for example biosynthesis of cell walls. Targeting these two genes plays a role to inhibiting the bacterial growth of E. coli.